Design principles for e-learning platforms featuring higher-education students' enterprise systems end-user training - Mareen Wienand; Tobias Wulfert; Hiep Hoang (Springer, 2024)
Abstract Enterprise systems are complex information systems that are inevitable for companies' success. As enterprise systems are only successful when used continuously and efficiently by end-users, knowledge on how to use them has become an important skill for employees. Research and practice favor an early obtainment of these skills for employees. Thus, it is usual to train students in enterprise systems usage before they start their professional career. Even though in organizational settings e-learning based approaches gain momentum, adapting design instances of multi-purpose platforms like Udacity, Udemy or Coursera existing approaches directed at students are scarce. Nevertheless, a well-informed e-learning platform design can support the learning process. Therefore, we investigate the design of e-learning platforms featuring students' enterprise system end-user training. To address the lack of guidance on designing such e-learning platforms, we proposed four meta-requirements and ten design principles to increase students' learning success on e-learning platforms focusing on students' end-user training. To achieve this goal and to ground our results on empiricism, we collected data about e-learning-platform design from three data sources: (1) We reviewed the existing literature, (2) carried out a multi-case analysis, and (3) derived insights from implementing an e-learning platform for students' end-user training and thereby demonstrating the applicability of the design principles. Finally, we evaluated the implementation. Following the design principles, learning success should be increased by a flexible learning environment with easy access and use, propelled motivation, and fostered information exchange.